The Impacts of Marketing Capabilities on Business Performance in the Case of Selected Manufacturing firms in Ethiopia: The Mediating Role of Sustainable Competitive Advantage - Andualem Imiru, Getie (British Journal of Marketing Studies, 2024)
This study investigates the relationship between marketing capabilities, sustainable competitive advantage, and business performance within selected manufacturing firms in Ethiopia. Its primary objective was to explore the mediating role of competitive advantage between marketing capabilities and business performance. A total of 280 questionnaires were distributed, with 219 completed responses, yielding an 84% response rate. Participants were selected using purposive sampling. The study tested 20 hypotheses related to various marketing capability dimensions, including Market Sensing, Specialized Marketing Capabilities, Architectural Marketing Capability, and Dynamic Marketing Capabilities. A quantitative research methodology, using survey data, was employed to test these hypotheses. The findings revealed that several marketing capabilities, including Market Information Scanning, Pricing Capability, Channel Management Capability, and Customer Relationship Marketing, significantly impact business performance. Moreover, competitive advantage was found to mediate the relationship between marketing capabilities and business performance. These results emphasize the importance for manufacturing firms to prioritize the development of specific marketing capabilities to enhance performance and achieve sustainable growth in competitive markets. However, the study also found that Market Information Interpretation, Product Management Capability, Market Learning Capabilities, and Capability Enhancement did not significantly affect business performance, contrary to previous studies both locally and globally. The study's focus on manufacturing firms in Ethiopia limits the generalizability of its findings to firms in different industries or of varying sizes. Future research should explore the influence of firm size on the mediating effect of competitive advantage and further investigate under-explored constructs such as Market Information Interpretation and Product Management Capability. These insights can inform policymakers and practitioners in developing strategies tailored to the unique challenges faced by firms in emerging economies.